ANCD thrombectomy device: in vitro evaluation. (13th June 2019) - Sanchez, Sonia; Cortiñas, Ignacio; Villanova, Helena; Rios, Anna; Galve, Iñaki; Andersson, Tommy; Nogueira, Raul; Jovin, Tudor; Ribo, Marc
Abstract : Introduction: Endovascular treatment of stroke, although highly effective, may fail to reach complete recanalization in around 20% of cases. The Advanced Thrombectomy System (ANCD) is a novel stroke thrombectomy device designed to reduce clot fragmentation and facilitate retrieval by inducing local flow arrest and allowing distal aspiration in combination with a stent retriever. We aimed to assess the preclinical efficacy of ANCD. Methods: Soft red blood cell (RBC)-rich (n=20/group) and sticky fibrin-rich (n=30/group) clots were used to create middle cerebral artery (MCA) occlusions in two vascular phantoms. Three different treatment strategies were tested: (1) balloon guide catheter + Solitaire (BGC+SR); (2) distal access catheter + SR (DAC+SR); and (3) ANCD+SR, until complete recanalization was achieved or to a maximum of three passes. The recanalization rate was determined after each pass. Results: After one pass, ANCD+SR resulted in an increased recanalization rate (94%) for all clots together compared with BGC+SR (66%; p<0.01) or DAC+SR (80%; p=0.04). After the final pass the recanalization rate increased in all three groups but remained higher with ANCD+SR (100%) than with BGC+SR (74%; p<0.01) or DAC+SR (90%; p=0.02). The mean number of passes was lower with ANCD+SR (1.06) than with BGC+SR (1.46) or DAC+SR (1.25) (p=0.01). A logistic regression model adjusted for treatment arm, clot type, and model used showed that both RBC-rich clots (OR 8.1, 95% CI 1.6 to 13.5) and ANCD+SR (OR 3.9, 95% CI 1.01 to 15.8) were independent predictors of first-pass recanalization. Conclusion: In in vitro three-dimensional models replicating MCA-M1 occlusion, ANCD+SR showed significantly better recanalization rates in fewer passes than other commonly used combinations of devices.